An Overview on Probiotics (International Journal of Food and Nutritional Sciences, 2022)
Probiotic bacteria have grown in popularity over the past two decades as a consequence of mounting scientific data demonstrating their positive benefits on human health. There is scientific data that suggests including probiotics into one's diet may provide health advantages. When it comes to the prevention and treatment of some diseases, this data seems sufficient, but when it comes to others, it appears promising or even contentious. As a consequence, they've been used in a variety of goods, with the food sector playing a key role in researching and marketing them. Probiotics have been used in a variety of goods, mostly fermented dairy foods, in this market. Given this tendency, and despite solid scientific evidence linking these microbes to a variety of health advantages, further study is required to establish them and assess their safety as well as nutritional elements. The aim of this article is to examine the existing research on the idea of probiotic bacteria and their potential beneficial qualities, with an emphasis on those found in food.